Music for Two Pianos, Piano Duets [de Wolfgang Amadeus Mozart] = Werke für Klaviere und für Klavier zu vier Händen [de Wolfgang Amadeus Mozart] = Musique pour deux pianos et pour piano à quatre mains [de Wolfgang Amadeus Mozart] = Musica per due pianoforte e per pianoforte a quattro mani [de Wolfgang Amadeus Mozart] - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: 1) Sonata in C for Piano, KV 19d; 2) Sonata in D for Piano Duet, KV 381/124a; 3) Sonata in B Flat for Piano Duet, KV 358/186c; 4) Sonata in D for Two Pianos, KV 448; 5) Fugue in C Minor for Two Pianos, KV 426; 6) Larghetto and Allegro in E Flat for Two Pianos, KV deest; 7) Sonata in F for Piano Duet, KV 497; 8) Sonata in G for Piano Duet, KV 357/497a+500a; 9) Andante with Five Variations in G for Piano Duet, KV 501; 10) Sonata in C for Piano Duet, KV 521.